Controlled Grafting of Cellulose by Atom Transfer Radical Polymerization of Butyl Methacrylate - Maimaiti, Halidan; Aerken, Xuekelaiti (Asian Journal of Chemistry, 2014)
Through atom transfer radical polymerization (ATRP) in the solution of 1-allyl-3-methylimidazolium chloride (BMIMCl), which is ionic, cellulose graft poly(butyl methacrylate) copolymers (Cell-PBMA) were prepared. The macroinitiator cellulose chloroacetate (Cell-ClAc) was synthesized through direct acylation of cellulose with chloroacetyl chloride (ClCH2COCl) in 1-allyl-3-methylimidazolium chloride. Afterward, the synthesized Cell-ClAc was used for the ATRP of butyl methacrylate (BMA) mediated by the CuCl and four-dimethyl aminopyridine (DMAP) catalytic system. Employing techniques such as FTIR and NMR, the Cell-ClAc and Cell-PBMA were characterized. Gel permeation chromatography (GPC) was employed for the analysis of the characteristics of the polymerization and the polymer molecular weights distribution. With contact angle measurements, the hydrophobicity of Cell-PBMA was studied. The study demonstrated that the graft copolymerization of Cell-PBMA is a controlled/‘living’ radical polymerization and the obtained graft polymer has a significant hydrophobic performance, indicating its potential applications as an oil absorption material.